Power spectra of infragravity waves in a deep ocean. Issue 10 (29th May 2013) - Godin, Oleg A.; Zabotin, Nikolay A.; Sheehan, Anne F.; Yang, Zhaohui; Collins, John A.
Abstract: [1] Infragravity waves (IGWs) play an important role in coupling wave processes in the ocean, ice shelves, atmosphere, and the solid Earth. Due to the paucity of experimental data, little quantitative information is available about power spectra of IGWs away from the shore. Here we use continuous, yearlong records of pressure at 28 locations on the seafloor off New Zealand's South Island to investigate spectral and spatial distribution of IGW energy. Dimensional analysis of diffuse IGW fields reveals universal properties of the power spectra observed at different water depths and leads to a simple, predictive model of the IGW spectra. While sources of IGWs off New Zealand are found to have a flat power spectrum, the IGW energy density has a pronounced dependence on frequency and local water depth as a result of the interaction of the waves with varying bathymetry. Key Points: Infragravity waves couple wave processes in oceans, atmosphere, and solid Earth Invariant property of IGW power spectra is observed in a large‐scale experiment We derive first model of spectral and spatial energy distribution of IGW energy